Critical Evaluation of Global Infection Prevention and Control Guidelines for Dentistry Published during the First 2 Years of the COVID-19 Pandemic - Khlood Alkurdi; Rowaina Mansouri; Aseel Ismail; Noha Seoudi (International Journal of Dentistry)
Objectives. The outbreak of the coronavirus disease (COVID-19) encouraged immediate actions by governments and healthcare associations across the world to flatten the curve and prevent health systems from being overburdened. As dentistry comprises aerosol-generating procedures (AGPs), which could increase the risk of infection, various guidelines were issued for dental services which focused on infection prevention and control (IPC) measures for COVID-19. This systematic review focuses on dental IPC guidelines, with the aim of comparing these guidelines against a gold standard. Method. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist was employed. Predefined inclusion and exclusion criteria were constructed. Information sources comprised Google Scholar, PubMed, and a manual search from December 2019 to December 2021. The Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument was used. Consensus scoring was applied for all guidelines. Results. A total 61 guidelines were included in the review. The UK national guideline was used as a gold standard as it ranked the highest AGREE score (75 out of 84) and thus was established for comparison with each of the included guidelines. Overall, 40% of the included guidelines had a high consensus score in relation to the UK national guideline. Conclusion. This systematic review highlighted the variability in content and quality of advice given by different organizations in response to the COVID-19 pandemic in their efforts to reduce SARS-CoV-2 transmission in dentistry. Establishing a single worldwide fast-acting dental organization would ensure that high-quality standardized guidance is available, to enhance health equality and worldwide dental clinical standards.